Diseño De Un Futuro Sostenible A Través De 3 Viviendas Bioclimáticas Personalizadas Para Poblaciones Discriminadas En Ibagué Tolima Colombia (2023)
Considering that until today, a project has not been carried out in which the design of housing for residents with different peculiarities in their way of living and acting is considered from architecture, which has led them to be censored, excluded and repudiated by society , who does not conceive of living with noise, different odors and substances that affect the senses, this research proposal is presented, which includes the problem felt by a minority of inhabitants and leads it to the design of a house that takes advantage of bioclimatic determinants, to accommodate the spaces in accordance with them; and it also makes it possible to make housing a sustainable place through the good use that residents make of water and energy resources, experiencing their economy. On the other hand, for the realization of this work, the methodology has been taken into account, whose exploratory scope reveals a new theme in the field of research, a qualitative approach within an action research design, in which participation is given to the community that provides the necessary information that is included in the proposal to substantiate the need and the case studies